The Normative Nature of Depression Among Impoverished Mothers of Color: ". . .going around this big old circle . . . it always remain the same". Issue 2 (April 2019) - Keefe, Robert H.; Rouland, Rebecca S.; Lane, Sandra D.; Brownstein-Evans, Carol; Larrison, Christopher R.; Delmerico, Alan M.
Perinatal depression among impoverished mothers adds an enormous burden to their family responsibilities, which are often further stressed by living in high-crime communities. Thirty impoverished mothers of color living with depression were interviewed about the difficulties they face raising their children. Qualitative interviews about living with depression revealed four themes: recognizing their own depression, feeling isolated, experiencing violence, and living with depression. This article examines how neighborhood and relationship violence, intermittently involved fathers, and isolation contribute to the mothers' depression. Social workers working with depressed, low-income mothers of color can benefit from understanding the mothers' lived experience and the barriers the mothers face while trying to achieve well-being for themselves and their children. This study fits within the "Close the Health Gap" area of the Grand Challenges for Social Work.